Exploratory Study about Health and Job Stress Determinants for Teaching and Research Staff in Universities in Spain - Saura, Maria Jose; Simo, Pep; Enache, Mihaela; Fernandez, Vicenc (Education Policy Analysis Archives, 2011)
The legal changes in the hiring profiles of universities in Spain implied significant changes in the processes of employment, stabilization and promotion of their academic staff. The aim of this research is to identify the antecedents of health and job stress of this staff, which traditionally experimented low levels of these indicators. The empirical research was based on an exploratory study that combined quantitative (questionnaires) and qualitative (cognitive interviews) data gathered from 26 cases representing three different academic positions: teaching assistants, post-dissertation teaching assistants and tenured PhD lecturers. This paper proposes a health and job stress model with five dynamics: justice, permanence commitment, time, and demands and resources related with the teaching and research staff assessment process. The findings indicate that the last two dynamics (demands and resources) are mediated by the insecurity construct. This model allows comparing the classical models of job stress with the new scenario of the Spanish universities and represents a first step for the development of more efficient human resource practices in universities.﻿